Cancer surveillance awareness and practice among families at increased risk for pancreatic adenocarcinoma. Issue 13 (15th March 2021) - Everett, Jessica N.; Burgos, Gabriela; Chun, Jennifer; Baptiste, Ariele; Khanna, Lauren G.; Oberstein, Paul E.; Simeone, Diane M.
Abstract : BACKGROUND: Early detection of pancreatic ductal adenocarcinoma (PDAC) is an important goal for improving survival. Individuals who meet published guidelines for surveillance may be underidentified, and family communication about risk represents a pathway to increasing participation in surveillance. We investigated the uptake of and barriers to surveillance in at‐risk relatives of clinic patients. METHODS: We conducted a retrospective record review of patients with personal or family history of PDAC evaluated over 12 months. The first relative presenting to clinic (proband) reported surveillance status and reasons for nonparticipation for at‐risk relatives. Descriptive analyses and Fisher's exact tests were conducted to evaluate differences in surveillance participation. RESULTS: Among 193 at‐risk relatives, 21% were in surveillance. The primary reasons for nonparticipation were lack of awareness (36%) and lack of interest (24%). Neither the sex nor the cancer status of probands impacted surveillance. At‐risk relatives with familial pancreatic cancer (FPC) who also carried relevant pathogenic germline variants (PGVs) were more likely to undergo surveillance than those with FPC or PGVs alone ( P = .003). Among families with PGVs, 59% of relatives potentially eligible for surveillance had not completed genetic testing. CONCLUSION: PDAC surveillance is underutilized in high‐risk families. Communication interventions to address informational needs and decisional support could improve outcomes. Abstract : Pancreatic cancer surveillance is underutilized in high‐risk families. Interventions to address family communication, informational needs, and decisional support are warranted for families at high risk for pancreatic cancer.